2018
DOI: 10.1002/aic.16333
|View full text |Cite
|
Sign up to set email alerts
|

Promoted adsorption of CO2 on amine‐impregnated adsorbents by functionalized ionic liquids

Abstract: Amine‐impregnated adsorbents are promising alternatives to aqueous amines for CO2 capture. However, the diffusion‐controlled CO2 adsorption process is a significant issue associated with them, resulting in the insufficient utilization of amine groups. Herein, we propose the use of functionalized ionic liquids 1‐ethyl‐3‐methylimidazolium acetate ([emim][Ac]) with chemical reactivity to CO2 and low viscosity as the additive to amine‐impregnated adsorbents. The key is that [emim][Ac] does not show drastic increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
50
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(53 citation statements)
references
References 33 publications
1
50
0
Order By: Relevance
“…The SO 2 /CO 2 selectivityof the adsorbent synthesized by the impregnation method was 396 under 50 C and 0.10 MPa, which is much higher than that of the adsorbent synthesized by the grafting method. The similar conclusions for [C 2 mim][OAc]@SBA-1587 and [C 2 mim][OAc]@MOF-17788 were also obtained.The AA-functionalized ILs containing amino groups and carboxyl groups are the desired choice to prepare IL hybrid materials to capture CO 2 as well. Uehara et al89 synthesized six supported AAfunctionalized IL adsorbents to explore the influence of anions and cations on CO 2 adsorption performances, which were [C 2 mim][Gly]@ polymethyl methacrylate (PMMA), [C 2 mim][Lys]@PMMA, [C 2 mim] [His]@PMMA, [P 4444 ][Gly]@PMMA, [P 4444 ][Lys]@PMMA, and [P 4444 ] [His]@PMMA.…”
supporting
confidence: 81%
“…The SO 2 /CO 2 selectivityof the adsorbent synthesized by the impregnation method was 396 under 50 C and 0.10 MPa, which is much higher than that of the adsorbent synthesized by the grafting method. The similar conclusions for [C 2 mim][OAc]@SBA-1587 and [C 2 mim][OAc]@MOF-17788 were also obtained.The AA-functionalized ILs containing amino groups and carboxyl groups are the desired choice to prepare IL hybrid materials to capture CO 2 as well. Uehara et al89 synthesized six supported AAfunctionalized IL adsorbents to explore the influence of anions and cations on CO 2 adsorption performances, which were [C 2 mim][Gly]@ polymethyl methacrylate (PMMA), [C 2 mim][Lys]@PMMA, [C 2 mim] [His]@PMMA, [P 4444 ][Gly]@PMMA, [P 4444 ][Lys]@PMMA, and [P 4444 ] [His]@PMMA.…”
supporting
confidence: 81%
“…As for N 2 adsorption, 3D‐NHPC‐x display much lower capacities. The corresponding CO 2 /N 2 selectivity of synthesized 3D‐NHPC‐x for CO 2 and N 2 (0.15/0.85 v/v) at 1.0 bar was then estimated based on Ideal Adsorption Solution Theory (IAST) [63–68] . The determined results were in the range of 67.3∼83.5 at 0 °C, and 105.2∼131.8 at 25 °C (Table 2), which were much higher than various nitrogen‐doped porous materials [69–73] .…”
Section: Resultsmentioning
confidence: 97%
“…revealed that CO 2 adsorption capacity of [DMEDAH] + [Ac] -@activated carbon (AC) enhanced from 0.08 mmol/g (pure AC) to 0.77, 0.87, and 0.36 mmol/g with 10, 20, and 30 wt.% IL loadings at 298 K and 1 bar. Similarly, Liu et al[8] reported 80 % improvement in CO 2 adsorption capacities of polyetherimide (PEI)/SBA-15 composites with the impregnation of [EMIM] + [Ac] -(from 1.18 to 2.20 mmol/g) at 303 K. Considering high adsorption capacities of acetate-and sulfonate-based ILs for acidic gases, and their outstanding adsorption-based separation performances as impregnated into porous solids, the investigation of adsorption capacities of pristine acetate-and sulfonate-based ILs for the ternary mixture of CO 2 , H 2 S, and CH 4 is emerged due to the determination of their actual performance. Since especially, the selective adsorption of H 2 S and CO 2 from CH 4 by ILs impregnated into different solid and polymeric materials is of great significance, it is required initially to understand the structure-property relationship of pristine ILs for acidic gas separation.…”
mentioning
confidence: 87%
“…[3][4]. In this sense, superior acidic gas adsorption performance of ILs from biogas had led their widespread use in several separation processes by the impregnation in nanoporous solids, which is accepted as a promising strategy to design new surface properties within porous materials for gas adsorption [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%